2018
DOI: 10.1590/2179-8087.023916
|View full text |Cite
|
Sign up to set email alerts
|

Operational Performance of the Selective Cutting of Trees With Chainsaw

Abstract: The objective was to obtain a statistical model to estimate the operational performance of cutting trees with a chainsaw in the natural tropical forest north of Mato Grosso state. One-hundred-and-fifty-one operational cycles of selective logging for commercial purposes were registered. In each cycle, the effective time for cutting, the diameter of the trees, commercial height, the number of logs per tree, and the distance between trees was determined. A step-by-step regression analysis was performed to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(8 reference statements)
0
1
0
1
Order By: Relevance
“…Diameter at Breast Height (DBH)), species, number of trees per ha, cutting technique/ experience of operators, felling type (clear cut, systematic, selective thinning), felling intensity, stand type (evenly-aged high forest, coppice, etc. ), weather conditions and distance between trees can impact on the productivity of motor-manual felling (Sobhani, 1984;Peterson, 1987;Food and Agriculture Organization (FAO), 1998;Hartsough et al, 2001;Kleunder, Stokes, 1996;Wang et al, 2004;Ghaffariyan, Sobhani, 2007;Magagnotti et al, 2012;Balimunsi et al, 2011;Balimunsi et al, 2012;Borz, Ciobanu, 2013;Ignea et al, 2017;Acosta et al, 2018). It should be noted that felling is one of the riskiest components of harvesting operations.…”
Section: Work Productivity For Motor-manual Fellingmentioning
confidence: 99%
“…Diameter at Breast Height (DBH)), species, number of trees per ha, cutting technique/ experience of operators, felling type (clear cut, systematic, selective thinning), felling intensity, stand type (evenly-aged high forest, coppice, etc. ), weather conditions and distance between trees can impact on the productivity of motor-manual felling (Sobhani, 1984;Peterson, 1987;Food and Agriculture Organization (FAO), 1998;Hartsough et al, 2001;Kleunder, Stokes, 1996;Wang et al, 2004;Ghaffariyan, Sobhani, 2007;Magagnotti et al, 2012;Balimunsi et al, 2011;Balimunsi et al, 2012;Borz, Ciobanu, 2013;Ignea et al, 2017;Acosta et al, 2018). It should be noted that felling is one of the riskiest components of harvesting operations.…”
Section: Work Productivity For Motor-manual Fellingmentioning
confidence: 99%
“…Previous research aimed at studying productivity costs of chainsaw logging has confirmed the influence of DBH on the cutting and total felling time. Some of these studies were conducted in forests of Arkansas (Lortz et al, 1997), the Appalachian Mountain, USA (Wang et al, 2004), the Caspian Forests, Iran (Behjou, 2012;Jourgholami et al, 2013), and the state of Mato Grosso, Brazil (Acosta et al, 2018). However, comparing the time involved in directional felling operations is difficult given the differences in the execution methodologies (Câmpu & Ciubotaru, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…More specific aspects that can interfere with the quality of directional felling comprehend felling direction angles (Cedergren et al, 2002;Krueger, 2004), the time used in the procedures (Lortz et al, 1997;Câmpu & Ciubotaru, 2017;Acosta et al, 2018), and dendrometric variables (Koger, 1983;Jourgholami et al, 2013). Identifying the most relevant components of directional felling can help execute the operation with accuracy, safety, and control (Naghdi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan rata-rata waktu yang diperlukan untuk menebang pohon pada teknik penebangan konvesional lebih lama daripada teknik perbaikan maka dapat disimpulkan bahwa semakin tinggi rata-rata DBH pohon maka belum tentu menghasilkan rata-rata produktivitas penebangan yang tinggi, hal ini dikarenakan keterampilan operator ikut berpengaruh. Variabel DBH memiliki korelasi yang tinggi dengan waktu penebangan pohon, tetapi untuk nilai DBH yang sama tinggi komersial pohon mungkin sangat berbeda untuk setiap lokasi, yang secara langsung mempengaruhi perkiraan produksi (Acosta et al 2018). Batang pohon berukuran besar dapat menjadi penghalang penebangan saat menggunakan chainsaw.…”
Section: Produktivitas Penebanganunclassified